Assessment of immature platelet fraction and immature reticulocyte fraction as predictors of engraftment after hematopoietic stem cell transplantation. (28th July 2014) - Morkis, I. V. C.; Farias, M. G.; Rigoni, L. D. C.; Scotti, L.; Gregianin, L. J.; Daudt, L. E.; Silla, L. M. da R.; Paz, A. A.
Summary Introduction Engraftment is a critical milestone of the hematopoietic stem cell transplantation (HSCT) process. The immature platelet fraction (IPF) and immature reticulocyte fraction (IRF) are considered early indicators of bone marrow recovery. The objective of this study was to assess these parameters as predictors of HSCT engraftment. Methods Neutrophil and platelet engraftment were defined as the first of three consecutive days with an absolute neutrophil count >0.5 × 109/L or platelet count >20 × 109/L, respectively. The IRF cutoff was 12%. Two IPF cutoffs were used: >6.2% and >10%. Results The study sample comprised 44 patients, of whom 24 had undergone autologous HSCT and 20 had undergone allogeneic HSCT. Absolute neutrophil counts >0.5 × 109/L were preceded by IRF >12% in 86% of patients (38 of 44). Platelet counts >20 × 109/L were preceded by an IPF >6.2% in 90% of patients (37 of 41) and by an IPF >10% in 63% of patients (26 of 41). Conclusion The results show that IRF and IPF are engraftment predictors. Peak in IPF was observed before rise in platelet count, while IRF rises before absolute neutrophil count (ANC) and persists increased. This indicates that IRF and IPF can be considered as new tools for hematopoietic assessment after HSCT.